A study to assess the prevalence of behavioral risk factors for lifestyle diseases among late adolescents in Chennai, Tamil Nadu - Mary A., Evangeline; P., Seenivasan; R. I., Shibiyeswanth; V., Prakash; S., Solaimuthurajagopal; N. C., Valaiyapathy (International Journal Of Community Medicine And Public Health, 2017)
Background: Lifestyle diseases are now the major causes of premature morbidity, mortality, and economic loss in developed and developing countries, including the younger age groups.The four major preventable behavioral risk factors are tobacco use, unhealthy diet, physical inactivity and harmful use of alcohol. Life of adolescents is a transitional period, offering them good opportunities for establishing health-promoting lifestyles. This study is done to assess the prevalence of behavioral risk factors for lifestyle diseases of college going adolescents of Chennai. Methods: This cross-sectional study was conducted among 483 randomly selected undergraduate students from randomly selected colleges in Chennai between March and September 2016 by two stage stratified sampling method using a semi-structured questionnaire. Data was fed into excel sheet and Descriptive and inferential statistical analysis was done using SPSS v.21 package. Results: The participants were between 17 and 20 years. They belonged to professional and non professional colleges. 78% students had unhealthy lifestyle habits. All the participants had at least one risk factor in them. The awareness on the risk factors was significantly less among non professional students, but they had significantly better behavioural habits than the professional students. Boys had significantly better habits than girls and students who were overweight significantly had unhealthy lifestyle habits. Conclusions: The study reflects the poor lifestyle habits of all college-aged individuals, which can be effectively improved by health education and behaviour change communication.